The innovator's cookbook - Johnson, Steven, 1968-; Heyborne, Kirby (Tantor Media, Inc., 2011)
Steven Johnson, an acknowledged bestselling leader on the subject of innovation, gathers-for a foundational text on the subject of innovation-essays, interviews, and cutting-edge insights by such exciting field leaders as Peter Drucker, Richard Florida, Eric Von Hippel, Dean Keith Simonton, Arthur Koestler, John Seely Brown, and Marshall Berman. Johnson also provides new material from Marisa Mayer of Google, Twitter's Biz Stone and Jack Dorsey, and Ray Ozzie, Microsoft's former chief software architect. With additional commentary by Johnson himself, this book reveals the innovation found in a wide range of fields, including science, technology, energy, transportation, education, art, and sociology, making it vital, fresh, and fascinating reading for our time, and for the future.